Lepirudin prevents lethal effects of Shiga toxin in a canine model - Raife, Thomas; Friedman, Kenneth D.; Fenwick, Brad (Thrombosis and Haemostasis, 2004)
Microvascular thrombosis is a major cause of organ damage in Shiga toxin-mediated hemolytic uremic syndrome (Stx-HUS). In vitro and clinical studies implicate thrombin-mediated mechanisms in the pathogenesis of Stx microvascular thrombosis. In a greyhound model, administration of 0.03μg/kg to 0.05μg/kg Stx1 or Stx2 causes severe bloody diarrhea and HUS with microvascular thrombosis requiring humane euthanasia within 65 hours. Using a greyhound model of Stx-HUS we analyzed early hemostatic changes, and tested the hypothesis that thrombin blockade with lepirudin would prevent lethal Stx effects. Two Stx1-exposed greyhounds were analyzed for hemostatic changes prior to onset of clinical manifestations. Serial hemostasis studies after Stx1 challenge revealed trends of increased aPTT, fibrinogen levels, and prothrombin fragment 1+2, and appearance of abnormally large von Willebrand factor multimers. Three greyhounds were anticoagulated with lepirudin to maintain activated partial thromboplastin times (aPTT) >2.5-fold normal, followed by administration of Stx2 and observation of clinical responses. Among the 3 lepirudin-treated, Stx2-challenged greyhounds, one developed severe illness requiring euthanasia. Remarkably, 2 of the 3 greyhounds developed only hypersalivation and restlessness that resolved (P <.03 compared to 14 historical controls). These two greyhounds were clinically, hematologically and biochemically normal 74 hours after Stx administration, well beyond the time of euthanasia of any previous greyhound. This study suggests that greyhounds exposed to Stx develop procoagulant changes similar to humans, and that thrombin may be a critical factor in the pathogenesis and treatment of Stx-HUS.
Keywords: Shiga toxin; lepirudin; thrombotic microangiopathy; procoagulant